Una reflexión crítica sobre ciudad educadora - Salcedo, Marco Alexis (Universidad de San Buenaventura - Cali, 2017)
The following text discusses the nature of the discussion that sets the document educating city, concluded that this is fundamentally ideological. It is noted that there is little analysis of the budgets-which have not been justified nor analyzed either philosophically or scientifically-primarily because the idea is in a very nascent stage that has not permitted the application of the principles and critical values that it is supporting, not necessarily because it was formalized in 1990, in the meeting held in Barcelona.